2014
DOI: 10.1039/c3cc48392d
|View full text |Cite
|
Sign up to set email alerts
|

A disk-aromatic bowl cluster B30: toward formation of boron buckyballs

Abstract: The B30 boron cluster has a bowl rather than a double-ring or a triple-ring tubular structure. This bowl isomer exhibits disk-aromaticity similar to that found for B20(2-) and B19(-) clusters. We confirmed that the concept of disk-aromaticity can be applied to both planar and non-planar systems.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
39
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 78 publications
(42 citation statements)
references
References 30 publications
3
39
0
Order By: Relevance
“…However, this structure is found to be the global minimum for neutral [B 30 ] ( Figure S2), as reported in a recent theoretical study. [28] Such divergence in global minimum structures for anions and neutrals has been observed previously for [B 20 ] and [B 22 ], [6,15] whose global minima were found to be planar in the anions, but the double rings in the neutral. However, no experimental evidence is available for the predicted neutral structures.…”
supporting
confidence: 56%
See 1 more Smart Citation
“…However, this structure is found to be the global minimum for neutral [B 30 ] ( Figure S2), as reported in a recent theoretical study. [28] Such divergence in global minimum structures for anions and neutrals has been observed previously for [B 20 ] and [B 22 ], [6,15] whose global minima were found to be planar in the anions, but the double rings in the neutral. However, no experimental evidence is available for the predicted neutral structures.…”
supporting
confidence: 56%
“…A pair of enantiomers characterized by different positions of the hexagonal hole on the quasi-2D molecular plane is found to be the global-minimum structures of [B 30 ] À , even though neutral [B 30 ] is found to have a bowl-shaped global minimum with a pentagonal hole, in agreement with a recent computational study. [28] The chiral [B 30 ] À cluster can be viewed as removing six atoms from the edge of the hexagonal [B 36 ] À , followed by a slight structural rearrangement.…”
mentioning
confidence: 99%
“…Herein we present a joint photoelectron spectroscopy (PES) and theoretical study of [B 30 ] − , which is found not only to feature a hexagonal hole but also to have a unique chiral structure. A pair of enantiomers characterized by different positions of the hexagonal hole on the quasi‐2D molecular plane is found to be the global‐minimum structures of [B 30 ] − , even though neutral [B 30 ] is found to have a bowl‐shaped global minimum with a pentagonal hole, in agreement with a recent computational study 28. The chiral [B 30 ] − cluster can be viewed as removing six atoms from the edge of the hexagonal [B 36 ] − , followed by a slight structural rearrangement.…”
Section: The Observed Vertical Detachment Energies (Vde) For [B30]− Csupporting
confidence: 86%
“…Isomer IX, which is highly non‐planar with a bow‐structure and a pentagonal hole, is 16.75 kcal mol −1 above the global minima. However, this structure is found to be the global minimum for neutral [B 30 ] (Figure S2), as reported in a recent theoretical study 28. Such divergence in global minimum structures for anions and neutrals has been observed previously for [B 20 ] and [B 22 ],6, 15 whose global minima were found to be planar in the anions, but the double rings in the neutral.…”
Section: The Observed Vertical Detachment Energies (Vde) For [B30]− Csupporting
confidence: 84%
“…a disk-aromatic bowl cluster B 30 . 60 Chemical bonding analysis reveals that delocalized multicenter-two-electron (nc-2e) σ and π bonds in all boron system stabilize the clusters, which makes the formation of metal-doped boron cluster available. 56 The boron-ligand metal compounds of wheel-type 61-65 and bowl-shape 66,67 have been reported.…”
Section: Introductionmentioning
confidence: 99%